Padepokan Karakter: Model of Character Development - Rachman, Maman; Munandar, Aris; Suhardiyanto, Andi (KOMUNITAS: INTERNATIONAL JOURNAL OF INDONESIAN SOCIETY AND CULTURE, 2015)
This study was aimed at describing the portraits of the factual management model of character reinforcement applied nowadays, developing the hypothetical management model of character reinforcement in Padepokan Karakter or a character hermitage. This research was conducted under research and development approaches. The subjects of this research were the informants (students, lecturers, teachers, school principals), documents, and events. The data were collected through interviews, observations, documentations, considerations of specialists and practitioners, focused group discussions, and questionnaires. The results indicated that the factual model of character reinforcement was done by integrating characters on subjects described in the functions of planning, implementation, and evaluation. The development of management models of character reinforcement recommended in this research was managed through the function of planning, organizing, implementing and controlling the characters in the character hermitage. The device of character reinforcement available in the character hermitage was effective and influential to reinforce the students character.